The Effectiveness of Student Worksheet (Project-Based Learning) Based on The Values of Islamic Boarding School for The Biotechnology Subject to Train High School Students with Bioentrepreneuship Skills - Rinaldiyanti Rukmana; Endang Susantini; Ahmad Bashri (Jurnal Inovasi Pembelajaran Biologi, 2020)
This study aimed at describing the effectiveness of student worksheet with an approach of project-based learning for the conventional biotechnology subject to train high school students with bioentrepreneurship skills. This study used instructional development method initiated by Fenrich through several steps: analysis, planning, designing, developing, implementation, evaluation, and revision. The experiment was conducted to 20 students at the twelfth grade in the Islamic Boarding School of A. Wahid Hasyim Jombang. The effectiveness of the project-based learning was 9.7% out of 100%. Students response was 90.0% on the values of Islamic boarding school or pesantren which become the indicator of having the bioentrepreneuship skills based on the summary of Adabul ˜Alim Wal Mutaallim kitab (hard work, responsibility, tolerance/tasamuh). Also, the completion of entrepreneurship project was 89.55%. These results show that the student worksheet is effective.